(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
The aim of the present study was to design an oral sustained release matrix tablet of highly water soluble biguanide anti diabetic drug. The matrix tablets are prepared by melt granulation method using HPMC K 200M as hydrophilic drug release retarding polymer, and stearic acid as melt able binder as well as hydrophobic carrier. The drug and excipients compatibility was studied by FT – IR. The formulated matrix tablets were characterized for physical parameters and in vitro dissolution profile. FT – IR spectra revealed the absence of drug excipients interaction. The physical parameters of the tablets were found within the limits. The drug release kinetics demonstrated that by increasing the concentration of hydrophilic polymer and hydrophobic carrier the drug release rate was retarded proportionally. Kinetic modelling of in vitro release profile revealing that the drug release from the matrix tablets following first order kinetics, and the drug release mechanism of optimized (F7) formula following non fickian transport mechanism. Accelerated stability studies were performed according to ICH guide lines. Temperature 40±20 c and relative humidity 75±5% RH to study physical and chemical changes of formulation. No physical or chemical changes were observed after t accelerated stability studies.